O6-methylguanine methyltransferase in colorectal cancers: detection of mutations, loss of expression, and weak association with G:C>A:T transitions. Issue 6 (11th May 2005) - Halford, S; Rowan, A; Sawyer, E; Talbot, I; Tomlinson, I
Abstract : Background and aims: O 6 -methylguanine methyltransferase (MGMT) repairs inappropriately methylated guanine in DNA. MGMT mutations have not previously been reported in cancers, but in colorectal tumours MGMT promoter methylation is common and has been associated with increased G:C>A:T transitions, a high frequency of K-ras mutations, and low level microsatellite instability (MSI low). However, some have suggested that MGMT changes are background or secondary events, with little importance for tumorigenesis. Methods: We have analysed fresh frozen colorectal cancers and colorectal cancer cell lines for MGMT changes: mutations, allelic loss, and protein expression. Results: Six of 113 cancers harboured somatic missense MGMT mutations, at least three of which probably caused reduced MGMT function and were accompanied by silencing or loss of the wild-type allele. Cancers with pathogenic MGMT mutations tended to harbour G:C>A:T somatic mutations at other loci. Overall, MGMT expression was reduced or lost in more than half of the cancers. We found no association between MGMT expression and the somatic mutation spectrum at APC, beta-catenin, K-ras, or p53, but decreased MGMT expression was weakly associated with the presence of a G:C>A:T change at any one of these loci. Reduced MGMT expression was not however associated with an increased frequency of K-ras mutations or with MSI low. Conclusion: In summary, we found that mutation of MGMT contributes to decreased protein function. Our findings provide good evidence to show that MGMT changes, including methylation, are selected rather than background events, at least in some cases. Decreased MGMT expression or function probably has a weak or moderate effect on the mutation spectrum in colorectal cancers.